Pengaruh Kinerja Pegawai Terhadap Tingkat Kesejahteraan (Studi Kasus Dinas Tenaga Kerja Kota Pontianak Tahun 2021-2023) - Salani, Husin; Firayanti, Yuni; Tawil, Hamzah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of employee performance on the level of welfare at the Pontianak City Manpower Office in 2021-2023, the description of which is stored in the memories of the employees there and recorded in the daily work report (when they come to work) of each employee and the annual report (performance accountability report) reported to the government. The method used in carrying out this research is through a qualitative method and accompanied by a phenomenological approach technique because the objects studied are no more than forty potential sources and the results needed are sufficient to be obtained from only a few selected employees, as well as from observations to documentation of information that is estimated to be able to provide answers to this problem. From the results of this study, it was found that the performance of employees at the Pontianak City Manpower Office in 2021-2023 was proven to have an impact on their level of welfare, including additional funds for implementing the service, additional Employee Income (TPP), successful achievement of tasks and functions, always good physical condition, and good social relations. The results of this study are expected to become a science that can be emulated by workers such as employees, staff and others, both superiors and subordinates, and can be developed or utilized for those who want to research something related to this research.